Kajian Struktural Sastra Pada Cerpen Dua Orang Sahabat Karya A.A Navis - Ghina Ayu Salsabila; Rizka Maulidania; Aveny Septi Astriani (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2023)
The aim of this study is to analyze the structural aspects contained in the short story "Dua Orang Sahabat" by A.A Navis. The study was conducted by collecting data from the short story "Dua Orang Sahabat" using qualitative methods and the technique of analyzing structural aspects to analyze the short story. The data used was the short story "Dua Orang Sahabat" which is included in the collection of short stories entitled "Robohnya Surau Kami" by A.A Navis. The data was analyzed using a literary structural approach. The structural approach can be used to analyze the structure of literary works. By using the structural approach, readers can understand in detail, present, and unpack precisely and in detail so that the understanding of the meaning of literary works is more optimal. The results of the study indicate that there are structural elements in the short story "Dua Orang Sahabat", such as theme, character and characterization, point of view, setting, plot, style, and message. This study is expected to provide an overview of the structural aspects contained in the short story "Dua Orang Sahabat" by A.A Navis and can be a reference for readers to understand the content of the short story.